Factors contributing to energy loss in left ventricle during diastolic and systolic phases in elderly patients. Issue 1 (21st November 2020) - Futami, Shutaro; Ishikawa, Joji; Maeda, Teppei; Kawano, Masuyo; Sakurayama, Chieko; Harada, Kazumasa
Abstract: Background: The change of left ventricular function deteriorated with age because of gradual increases of blood pressure may result in increased energy loss (EL) in left ventricle (LV). The present study investigated EL in LV among hypertensive elderly patients and examined factors contributing to EL. Methods: A single‐center retrospective study was performed on elderly hypertensive outpatients (≥65 years) who underwent echocardiography ( N = 105). EL in the LV was measured using a vector flow mapping system, and factors affecting peak EL during the early‐diastolic phase (ED‐EL), late‐diastolic phase (LD‐EL), and systolic phase (Sys‐EL) were evaluated. Result: Mean age was 79.9 ± 6.4 years (male 43%). Mean ED‐EL, LD‐EL, and Sys‐EL were 42.1 ± 46.7, 75.6 ± 60.2, and 40.4 ± 40.2 mJ/N/s. In a stepwise regression analysis, the E/e'(lateral) (unstandardized B = 0.005, 95%CI −0.03 to 0.007, standardized β = 0.434, P < .001) was identified as factors affecting ED‐EL. The factors affecting LD‐EL were E/A ratio (B = −0.122, 95%CI −0.176 to −0.068, β = −0.470, P < .001) and time velocity integral (TVI) in LVOT (unstandardized B = 0.002, 95%CI 0.000 to 0.004, β = 0.247, P = .021). The factors influencing Sys‐EL were TVI in LVOT (B = 0.002, 95%CI 0.001 to 0.004, β = 0.390, P < .001), E/A ratio (B = −0.054, 95%CI −0.093 to −0.015, β = −0.258, P = .008), left ventricular outflow tract (LVOT) diameter (B = −0.006, 95%CI −0.010 to −0.002, β = −0.307, P = .006), and left ventricular mass index (B = 0.000, 95%CI 0.000 to 0.001, β = 0.208, P = .039). Conclusion: Peak EL in the LV was higher during diastolic phase than systolic phase among elderly hypertensive patients. Peak EL both during late‐diastolic phase and systolic phase was affected by systolic blood flow in LVOT and LV transmitral flow pattern.